Nano Influencer Analysis of Purchasing Interest in Micro and Small Business Products - Ardiansyah, Tedy; Nurjanah; Purwaningsih, Dewi; Hasan, Rahmawati (Yayasan Sinergi Kawula Muda, 2024)
This research aims to examine the influence of the nano influencer model innovation (ni) on purchasing decisions (kp) through consumer behavior (pk) and purchase interest (mb) on micro and small business or MSME products carried out in the media. In addition, this research also explores the mediating role of consumer behavior (pk) and purchase interest (mb) in relation to decision making (kp). using primary data collected in this research through a questionnaire clicked through Google Form by a total of 125 respondents. Sampling was carried out deliberately, with a focus on students who had experienced or had experience as influencers. Research findings show that ni, kp, and mb have a significant influence on kp in the Jakarta Bogor Depok Tanggerang Bekasi or JABODETABEK area. In addition, a significant influence of pk was found, and mb was identified as the main mediating factor between ni and kp, which were correlated with each other. This research presents the latest information and analysis regarding factors that can help students become nano influencers.